Analisis Kualitatif Strategi Skala Bisnis UMKM: Teknologi Tinggi vs Konservatif - Bahdin Nur Tanjung; Jumadiah Wardati; Agung Eko Puryanto (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2024)
This study qualitatively examines the comparative business-scaling strategies of MSMEs: a high-technology approach versus a conservative model. Amid ongoing digital transformation, MSMEs face the need to adapt in order to strengthen competitiveness. The high-technology strategy focuses on digital marketing and sales, product innovation driven by market-trend and customer-preference analysis, and operational efficiency through systems such as ERP to streamline supply-chain management. In contrast, the conservative model tends to maintain manual operational practices and conventional, offline marketing. Although it may provide operational stability, it often limits innovation, reduces responsiveness to market dynamics, and constrains access to digital segments. Data were collected through in-depth interviews, field observations, and document studies. The findings indicate that adopting a high-technology strategy can enhance business performance by expanding market reach, enabling product differentiation, and improving operational efficiency. However, it requires substantial initial investment and organizational culture change, which is not always easy for all MSMEs. Therefore, the study recommends an integrative model: selective/partial digital transformation in key areas such as marketing, data management, and product innovation—while preserving proven traditional operational foundations. This should be supported by strengthening digital literacy and human-capital capacity, as well as collaboration among MSMEs and communities to accelerate innovation and optimize performance